The Comparison of the US and EU Agricultural Antitrust Exemptions - Martin Milán Csirszki (Yearbook of Antitrust and Regulatory Studies, 2022)
The article aims to compare the sectoral antitrust exemption for agriculture that exists in the United States (US) and the European Union (EU). The roots for the privileged position of agriculture under antitrust laws date back to 1914. Section 6 of the Clayton Act was the first US law which exempted certain cooperatives. In 1922, the protection was extended to a broader range of agricultural entities by the Capper-Volstead Act. These two acts have since then determined the scope and extent of the US exemption but have evolved through judiciary interpretation. The EU has had a similar exemption for agriculture since the beginnings of European integration. After presenting briefly the likely explanations for the privileged treatment of this sector under antitrust, the article aims to analyse the regulations in force in order to explore their similarities and differences. The analysis also seeks to answer the question of whether the ‘accusation’ that EU competition law – in contrast with the US antitrust regime – is not purely based on efficiency considerations can also be extended to the agricultural sector’s privileged treatment. In the end, the rules in force of the two jurisdictions are compared and conclusions drawn.